Manajemen distribusi kapsul yodium pada ibu hamil di daerah endemik gangguan akibat kekurangan yodium (GAKY) di Kabupaten Gunung Kidul Provinsi Daerah Istimewa Yogyakarta - Hasrun Hasanu; Hamam Hadi; Toto Castro (Jurnal Gizi Klinik Indonesia, 2008)
Background: Iodine deficiency disorder (IDD) is a public health problem in Indonesia and this is closely related to intelligent and mental development disorder. Bad effect of IDD to pregnant mothers who suffer from serious IDD problem may happen during their second trimester pregnancy, however, such effect may be overcome by giving iodine substance supplement. Risks that may happen to pregnant mothers, especially to fetus and infants are miscarriage, stillbirth, born disabled, birth with low body weight, cretin, psychomotor disorder, and death in infancy. According to the result of IDD mapping, Total Goiter Rate at Gunung Kidul District is 12.6%. Short term effort to overcome IDD is distributing iodine capsule to the target, but there is problem in its implementation especially in the management process and resources.Objectives: To determine relationship between management factor and iodine capsule distribution coverage to pregnant mothers at IDD endemic area, Gunung Kidul District.Methods: The study was observational with cross sectional design which used both quantitative and qualitative approaches. Subjects were all nutrition staff and pregnant mothers at community health centers of IDD endemic areas at Gunung Kidul District.Results: There was significant relationship between iodine capsule intake status and urine iodine level (χ2=23.0 p<0.001). This showed that iodine capsule intake status could increase urine iodine excretion level of pregnant mothers. Management process (planning, implementation, control) had significant relationship with urine iodine excretion level of pregnant mothers subsequently (χ2=5.4, p=0.02, OR=1.86, χ2=16.64, p<0.001, OR=2.98, χ2=8.74, p=0.004, OR=2.23). This meant that good management process could increase iodine capsule intake status. Resources (human resources, facilities, fund) had significant relationship with iodine capsule intake status of pregnant mothers subsequently (χ2=4.65, p=0.043, OR=1.83, χ2=6.04, p=0.019, OR=1.94, χ2=6.04, p=0.019, OR=1.94). This showed that sufficient resources could increase iodine capsule intake status of pregnant mothers. Iodine capsule intake status of pregnant mothers was low, i.e. 86 persons of average 35.5% out of 263 respondents and median of urine iodine excretion of pregnant mothers belonged to IDD endemic category, i.e. 86.58 g/dL.Conclusion: Management process and resources had not functioned well and there was significant relationship between management process (planning, implementation, control); and resources (staff, fund, facilities) with coverage of iodine capsule distribution to pregnant mothers. Iodine capsule intake status of pregnant mothers tended to increase urine iodine excretion level of pregnant mothers.